Hak Asasi Manusia (HAM) Perspektif Al-Qur’an (Analisis Maqâshid Asy-Syarî’ah Dengan Pendekatan Tafsir) - Jufri Hasani Z (IAIN Batusangkar, 2021)
Humans as noble creatures have rights that must be given by various parties. Oppression, colonization and slavery and discrimination are forms of action that do not respect human rights. The sentence